Functional characterization of hypothetical proteins of Mycobacterium tuberculosis with possible esterase/lipase signature: a cumulative in silico and in vitro approach. Issue 6 (26th April 2017) - Kumar, Arbind; Sharma, Aashish; Kaur, Gurkamaljit; Makkar, Pooja; Kaur, Jagdeep
Abstract : The functional aspect of several mycobacterium proteins annotated as hypothetical are yet to be discovered. In the present investigation, in silico approaches were used to predict the biological function of some of the unknown Mtb proteins, which were further validated by wet lab experiments. After screening thousands of Mtb proteins, functionally unknown hypothetical proteins Rv0421c, Rv0519c, Rv0774c, Rv1191, Rv1592c, and Rv3591c were chosen on the basis of their importance in Mtb life cycle. All these proteins posses the α/β-hydrolase topological fold, characteristic of lipases/esterases, with serine, aspartate, and histidine as the putative members of the catalytic triad. The catalytic serine is located in pentapeptide motif "GXSXG" and oxyanion residue is in dipeptide motif HG. To further support our observation, molecular docking was performed with conventional synthetic lipolytic substrates (pNP-esterss) and specific lipase/esterase inhibitors (tetrahydrolipstatin and phenylmethanesulfonyl fluoride (PMSF)). Significant docking score and strong interaction of substrates/inhibitors with these proteins revealed that these could be possible lipases/esterases. To validate the in silico studies, these genes were cloned from Mtb genome and the proteins were over-expressed in pQE-30/ Escherichia coli M15 system. The expressed proteins were purified to homogeneity and enzymatic activity was determined using pNP esters as substrate. The enzyme activity of recombinant proteins was inhibited by tetrahydrolipstatin and PMSF pre-treatment. Outcome of the present investigation provided a basic platform to analyze and characterize unknown hypothetical proteins.